PERLINDUNGAN HAK KORBAN DALAM SISTEM PERADILAN PIDANA INDONESIA - Zulfa Asma Vikra (Yayasan Pendidikan Literasi Borneo, 2025)
This study aims to analyze the protection of victims’ rights within the Indonesian criminal justice system. This research employs normative legal research using statutory and conceptual approaches. The findings indicate that although regulations on victim protection have developed through the Witness and Victim Protection Act, their implementation remains ineffective. Victims are often positioned merely as supporting evidence providers and have not received comprehensive recovery. Therefore, strengthening a victim-oriented criminal justice paradigm through a human rights approach and restorative justice is essential to achieve substantive justice.